Testing and selection methods of low temperature rapid repair materials

Through screening and testing, a low-temperature rapid repair material with excellent performance in low-temperature environments of -10℃~-20℃ was determined, which solved the problem of repairing airport road surfaces in low-temperature environments, and achieved high-strength, durability and convenient construction effects.

CN119780398APending Publication Date: 2025-04-08CHINA RAILWAY BEIJING ENG GRP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510019038.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In low temperature environments, rapid repair materials for airport road surfaces need to have high flexural resistance, compressive strength, durability and adhesion, while not producing freezing and shrinking cracks, and are easy to construct.

Method used

Through systematic engineering experiments and research, a low-temperature rapid repair material was screened. The material maintained excellent performance under a negative temperature environment of -10℃ to -20℃, including final settling time of 30~40min, 4h flexural strength ≥5.0MPa, compressive strength ≥30.0MPa, good durability, strong adhesion, and easy to construct.

Benefits of technology

This low-temperature rapid repair material can effectively repair the airport road surface under a low temperature environment, ensuring that the flexural resistance and compressive strength meet the requirements after construction, and the material has good durability and does not cause freezing and shrinking cracks, making the construction simple and convenient.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119780398A_ABST
    Figure CN119780398A_ABST
Patent Text Reader

Abstract

The present invention discloses a method for testing and selecting low-temperature rapid repair materials, which is characterized in that it includes the following steps: S01, determining general test conditions; S02, classifying according to the depth of the pothole to be repaired, determining the low-temperature rapid repair material, and performing repair and performance tests; S03, selecting the low-temperature rapid repair material according to the obtained performance test results and the price of the low-temperature rapid repair material. The method for testing and selecting low-temperature rapid repair materials of the present invention determines general test conditions, and determines different low-temperature rapid repair materials for different repair depths, and performs different repair methods and performance tests, which can effectively test and select low-temperature rapid repair materials to meet the requirements of being suitable for use in an ambient temperature of ‑10 to ‑20°C without frost heave, meeting the requirements of flexural and compressive strength when open to traffic (within about 4 hours after construction is completed), simple and easy construction and operation, good material durability, strong adhesion, small drying shrinkage, and no shrinkage cracks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rapid road repair, and in particular relates to a method for testing and selecting low-temperature rapid repair materials. Background Art

[0002] As a key place for aircraft takeoff and landing, airports are responsible for ensuring the efficient transportation of personnel and materials. They are important infrastructure for ensuring aviation safety and safeguarding public interests. However, with the renewal of aircraft and the continuous growth of transportation volume, the service life of airport pavements is under great pressure, and the problem of pavement damage is becoming increasingly serious. On the other hand, the international environment is complex and changeable, and large hub airports and strategic airports may face potential security threats, resulting in pavement damage. Whether the pavement damage is caused by subjective or objective factors, the emergency repair and construction of airport pavements is crucial. Therefore, in-depth research on the rapid repair technology of airport pavements to ensure that the airport quickly resumes its ability to fly is not only of great significance to national security, but also a key link in maintaining social and economic stability.

[0003] In order to ensure the rapid repair of the pavement and the airport's ability to quickly resume navigation, the general principle is to use the old and quickly repair those that can be quickly repaired after evaluation; the plates with severe damage and no repair value will be directly replaced according to the new construction process standards. The temperature is expected to be -10℃, and then gradually drop to -20℃. The performance requirements for repair and grouting materials are extremely high, mainly in terms of strong low temperature adaptability (freezing resistance), fast early strength growth, good durability, small shrinkage, and strong adhesion. Summary of the invention

[0004] In order to ensure the smooth progress of the emergency repair and construction of the airport pavement, a systematic engineering test study was conducted to select an airport pavement repair material that can maintain excellent performance in a negative temperature environment of -10℃~-20℃. Its working performance should meet the requirements of final setting time of 30~40min, 4h flexural strength ≥5.0MPa, compressive strength ≥30.0Mpa, good durability, strong adhesion, no frost heave, small shrinkage, and easy construction. The selection requirements of pavement repair materials are suitable for an ambient temperature of -10~-20℃ without frost heave, and the flexural and compressive strengths meet the requirements when the traffic is open (within about 4 hours after the construction is completed); the construction is simple and easy to operate; the material has good durability, strong adhesion, shrinkage, and no shrinkage cracks.

[0005] The design requirements for low-temperature rapid repair materials are: final setting time of 30 to 40 minutes; 4h flexural strength ≥5.0MPa, compressive strength ≥30.0MPa; easy construction and workability and close to the color of the old concrete pavement; suitable for shallow and deep repairs with a depth of ≤50mm and >50mm. The repair material contains strong aggregates and should ensure a certain durability. It can be used after adding water and mixing on site; by adjusting the mix ratio or adding external admixtures (such as antifreeze agents), it will not frost heave when used in a scene of -10℃ to -20℃, or the strength can meet the requirements before frost heave occurs.

[0006] The present invention discloses a method for testing and selecting a low-temperature rapid repair material, comprising the following steps:

[0007] S01, determine the general conditions of the test;

[0008] S02, classify the potholes according to their depth, determine the low-temperature rapid repair material, and conduct repair and performance testing;

[0009] S03, select the low-temperature rapid repair material based on the performance test results and the price.

[0010] In some embodiments of the present invention, in S01, the general test conditions include at least one of the following:

[0011] (1) The external environment temperature of mixing and processing is 8-10℃;

[0012] (2) The mixing water is an ice-water mixture with a temperature of 0°C ± 2°C;

[0013] (3) The mixing and preparation time is 6 to 8 minutes, and the specimen size is 40 mm × 40 mm × 160 mm;

[0014] (4) After rapid molding, the molded specimens are placed in a freeze-thaw box at a temperature of -10 to -20°C, and strength tests are performed on the molded specimens after 2 h, 3 h, and 4 h.

[0015] In some embodiments of the present invention, in S02, the repaired pothole depth includes a shallow pothole repair depth of ≤5 cm and a deep pothole repair depth of >5 cm.

[0016] In some embodiments of the present invention, in S02, for shallow repair of potholes with a depth of ≤5 cm, a low-temperature rapid repair material without coarse aggregate is used, or a low-temperature rapid repair material without coarse aggregate is formed by removing coarse aggregate with a test sieve;

[0017] Preferably, a test sieve with a mesh size of 2.36 mm is used.

[0018] In some embodiments of the present invention, in S02, for deep repair of potholes with a depth of more than 5 cm, a low-temperature rapid repair material containing coarse aggregate, or a low-temperature rapid repair material without coarse aggregate and added with crushed stone is used;

[0019] Preferably, the crushed stone is a continuously graded crushed stone;

[0020] Preferably, the aggregate particle size in the low-temperature rapid repair material containing coarse aggregate is 4.75-9.5 mm.

[0021] In some embodiments of the present invention, in S02, for shallow repairs with a pothole depth of ≤5 cm, the performance test performed after the repair includes early strength;

[0022] Preferably, the early strength includes at least one of 2h, 3h compressive strength and 2h, 3h flexural strength.

[0023] In some embodiments of the present invention, in S02, for deep repairs with a pothole depth of more than 5 cm, the performance test performed after the repair includes at least one of early strength, shrinkage performance, initial setting and final setting time, workability and appearance;

[0024] Preferably, the early strength includes at least one of 2h, 3h, 4h compressive strength and 2h, 3h, 4h flexural strength;

[0025] Preferably, the working properties are early hydration heat, setting time, fluidity, and workability;

[0026] Preferably, the appearance includes the color difference with the original concrete and the adhesion between the new and old joint surfaces.

[0027] In some embodiments of the present invention, S02 includes the steps of repairing the surface, calculating the amount of materials, premixing the materials, optionally adding stones, adding water for mixing, and vibrating the surface;

[0028] Preferably, the repair surface treatment is to cut and remove the damaged part to the hard layer, and the depth of the removal is determined according to the actual situation. The surface of the pit after treatment shall not have cracks, loose gravel, floating dust, oil stains, and accumulated water;

[0029] Preferably, when the repair depth is ≥5cm, stones are added to make concrete, and the weight ratio of the repair mixture to stones is controlled at 100:50-80, and the stones are clean crushed stones with a continuous gradation of 5-30mm in particle size;

[0030] Preferably, 5.5% to 7% of water by weight of the low-temperature rapid repair material is added at one time and stirred until the mixture has good fluidity and cohesiveness;

[0031] Preferably, the evenly mixed material is placed into the pit to be repaired and compacted with a flat plate vibrator or a vibrating rod, and the surface is quickly prepared before initial setting.

[0032] In some embodiments of the present invention, in S02, the repair range extends 5 to 10 cm outward from the disease-affected area, and the repair size is a regular rectangle with a length-to-width ratio of less than 3:1;

[0033] Preferably, patches with irregular plane dimensions or a length-to-width ratio greater than 3:1 should be repaired in multiple times to ensure that each patch meets the size requirements; or they can be repaired in one go and cut promptly after pouring. After cutting, the patches should meet the requirement of a length-to-width ratio of 3:1.

[0034] In some embodiments of the present invention, S02 includes the steps of cleaning the damaged board surface, wetting and preheating the base surface, interface treatment, simple formwork, mixing the repair material, pouring the repair material, finishing and roughening, and curing;

[0035] Preferably, the crushing plate body is broken into small pieces by a pneumatic pick or electric hammer and then removed, loose materials on the surrounding plate body base surface are completely removed, and dust on the base surface and in the groove is blown away by a high-pressure blower;

[0036] Preferably, 0.5-1 hour before pouring the mixture, the base surface is fully moistened with warm water not exceeding 65°C and the exposed water is removed with a portable high-pressure hot air blower or the pre-treated base surface is heated with a gas torch;

[0037] Preferably, a layer of polymer interface agent is evenly applied on the base surface;

[0038] Preferably, for the cement concrete pavement panel to be repaired in the middle, the surrounding panel edges are used as templates; for the cement concrete pavement panel to be repaired at the edge, the three sides thereof use the surrounding panel edges as templates, the edges are supported by wooden or steel templates, and anti-leakage slurry measures are taken;

[0039] Preferably, according to the number of on-site pouring and pouring speed, the repair material is manually put into the forced mortar mixer, dry mixed for 10 seconds, weighed according to the water amount specified in the product, and mixed with water twice: add 2 / 3 water for the first time and mix for 30 seconds; add 1 / 3 water for the second time and mix for 150 seconds. After mixing, the repair material should be left to stand for 2 to 3 minutes, and then pour after the bubbles disappear;

[0040] Preferably, pour the material slowly and evenly with a pouring container to make it dense, and avoid hollowing during pouring; after pouring, smooth the top surface of the repair material; the time for each preparation and mixing of the repair material from the start of mixing to the end of pouring shall not exceed 30 minutes; the repair material that exceeds the time limit or whose fluidity does not meet the pouring requirements shall not be used any more;

[0041] Preferably, after pouring and flushing with the board surface, the surface is immediately closed and roughened along the texture direction of the road panel surface to maintain the overall aesthetics;

[0042] Preferably, straw mats or quilts are used to cover and keep warm for 2 to 4 hours.

[0043] Beneficial effects:

[0044] The testing and selection method of the low-temperature rapid repair material of the present invention determines the general conditions of the test, and determines different low-temperature rapid repair materials for different repair depths, and conducts different repair methods and performance tests, which can effectively test and select the low-temperature rapid repair material to meet the requirements of being suitable for an ambient temperature of -10 to -20°C without frost heave, meeting the requirements of flexural and compressive strength when open to traffic (within about 4 hours after construction is completed), simple and easy construction, good material durability, strong adhesion, small drying shrinkage and no shrinkage cracks.

[0045] The testing and selection method of the low-temperature rapid repair material of the present invention selects materials with suitable performance according to actual on-site application scenarios to ensure the quality of the project. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 A low-temperature rapid repair material according to one embodiment of the present invention;

[0047] Figure 2 for Figure 1 Technical parameters of low temperature rapid repair material;

[0048] Figure 3 For use Figure 1 Schematic diagram of the patch area segmentation for repairing with low-temperature rapid repair materials;

[0049] Figure 4 Another low-temperature rapid repair material according to one embodiment of the present invention;

[0050] Figure 5 A low-temperature rapid repair material is stirred according to one embodiment of the present invention;

[0051] Figure 6 A test piece according to an embodiment of the present invention is vibrated and formed;

[0052] Figure 7 A test piece according to an embodiment of the present invention;

[0053] Figure 8 for Figure 7 The specimens were placed in a freeze-thaw chamber;

[0054] FIG9 is a freeze-thaw box temperature control diagram of an embodiment of the present invention; wherein 9-1 to 9-3 are temperature display diagrams of the freeze-thaw box cooling process, and 9-4 is a temperature measurement diagram of the specimen;

[0055] FIG. 10 is a demoulding molding test piece according to an embodiment of the present invention; wherein 10-1 to 10-2 are demoulding molding test piece examples;

[0056] FIG11 is a 2h, 3h, and 4h strength test of an embodiment of the present invention; wherein 11-1 to 11-2 are the detection strength display interfaces of the compressive strength test of the specimen, 11-3 is the compressive strength test of the specimen, and 11-4 to 11-6 are the failure surface diagrams of the specimen after the flexural strength test;

[0057] Fig.12 A road panel according to an embodiment of the present invention is provided with a hole (depth 0-6 cm) cut out;

[0058] Fig.13 A machine-mixed low-temperature rapid repair material according to one embodiment of the present invention;

[0059] Fig.14 This is a manually mixed low-temperature rapid repair material according to one embodiment of the present invention;

[0060] Fig.14 This is a manually mixed low-temperature rapid repair material according to one embodiment of the present invention;

[0061] Fig.15 A simple repair for one embodiment of the present invention;

[0062] Fig.16 A repaired surface according to an embodiment of the present invention;

[0063] Fig.17 After 4 hours of chiseling, the new and old concrete surfaces are firmly bonded. DETAILED DESCRIPTION

[0064] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0065] Implementation Method 1

[0066] Through market research and joint trial matching and modulation with a number of material suppliers, the following three materials were preliminarily selected as the candidate materials for this emergency repair project.

[0067] Selected material 1

[0068] Product name: A+B two-component super fast hardening concrete repair king.

[0069] Applicable ambient temperature: -10℃~-20℃, initial setting time 10-15min.

[0070] Scope of application: repair and reinforcement of airports, roads, railways, ports and large equipment foundations.

[0071] Manufacturer: A company in Hangzhou.

[0072] The material Figure 1 As shown, it is A / B two-component, 25kg / bag.

[0073] 1. Product performance

[0074] (1) High flexural and compressive strength in the early stage, which can be quickly opened to traffic, and the strength increases steadily in the later stage;

[0075] (2) Excellent crack resistance, low shrinkage, and no need for special maintenance;

[0076] (3) It has strong bonding strength with the original cement concrete and steel, and its thermal expansion coefficient and elastic modulus are almost the same as those of ordinary concrete. The failure test section is located inside the original concrete;

[0077] (4) Good durability, good resistance to salt frost erosion and chemical corrosion;

[0078] (5) It has strong resistance to steel bar corrosion and can form a passivation film on the surface of the steel bar, effectively preventing harmful media from corroding the steel bar.

[0079] 2. Technical parameters (indicators) such as Figure 2 shown.

[0080] 3. Usage

[0081] (1) Repair surface treatment

[0082] Cut and remove the damaged area to the hard layer. The demolition depth is determined based on the actual situation, and the minimum depth is not less than 5cm. The surface of the pit after treatment shall not have cracks, loose gravel, floating dust, oil stains, stagnant water and other debris.

[0083] (2) Calculation of material consumption

[0084] 1m 3 = 2400kg to calculate the total amount of repair materials and gravel required.

[0085] ① When the repair depth is less than 5cm, use repair mortar for repair. The mix ratio of repair mortar is: material A: material B: water = 50:50: (5.5~6.5), that is, the water-cement ratio is 0.06.

[0086] ② When the repair depth is ≥5cm, add gravel to make concrete for repair. The repair concrete mix ratio is: material A: material B: gravel: water = 50:50: (50~80): (5.5~7.0), that is, the water-cement ratio is 0.07.

[0087] ③1m 3 The common mix ratio of repair materials is: 1400kg of Repair King (A+B), 950kg of gravel, and 84kg of water. The amount of Repair King used is about 60% of the total amount of repair materials (Repair King + gravel).

[0088] (3) Premixed materials

[0089] Mix Repair King A material and B material in a 1:1 ratio until the color of the mixture is consistent. If the total amount is large, the dry materials can be mixed in multiple times. All dry materials must be mixed well before adding water.

[0090] (4) Adding stones

[0091] When the repair depth is ≥5cm, add gravel to make concrete. The weight ratio of the repair mixture and gravel is controlled at 100:50~80. The gravel should be clean crushed stone with continuous grading of particle size 5-30mm.

[0092] (5) Add water and mix

[0093] Add 5.5% to 7% water to the total amount of the Xiu Xiu Wang mixture (material A + material B) at one time and stir thoroughly until the mixture has good fluidity and cohesiveness.

[0094] (6) Vibrating and tamping

[0095] Place the evenly mixed concrete into the pit to be repaired, and vibrate it thoroughly with a flat plate vibrator or vibrator to make it dense, and quickly prepare the surface before initial setting.

[0096] (7) Open traffic

[0097] The construction can be opened to traffic 1 to 2 hours after passing the strength test. No special maintenance is required during this period and do not water it.

[0098] 4. Maintenance size

[0099] (1) For partial thickness repair, the minimum repair depth is 5 cm, the maximum side length of the patch should not exceed 2 m, and the shortest side length should not be less than 0.15 m; for full thickness repair, the shortest side length of the patch should not be less than 60 cm.

[0100] (2) The repair area should extend 5 to 10 cm outward from the disease-affected area, and the repair size should be a regular rectangle with a length-to-width ratio of less than 3:1.

[0101] (3) For patches with irregular plane dimensions or a length-to-width ratio greater than 3:1, they can be repaired in multiple times to ensure that each patch meets the size requirements; or they can be repaired in one go and cut in time after pouring. After cutting, the patch should meet the requirement of a length-to-width ratio of 3:1 (see the figure below), and the cut seams should be grouted. Figure 3 shown.

[0102] 5. Application Cases

[0103] Pavement maintenance at Chongqing, Weihai, and Chengdu Shuangliu Airport, bridge deck maintenance at Ningbo-Taizhou-Wenzhou Expressway, Harbin-Tonghua Expressway, and Guangzhou-Shenzhen Expressway, Foxling Tunnel, Inner Mongolia Yellow River Bridge (-20℃), Urumqi viaduct bearing maintenance, Zhenjiang Port, and Shanghai Metro Line 12, etc.

[0104] Selected material 2

[0105] Product name: Airport special repair material (a certain model)

[0106] Applicable ambient temperature: -10℃~-20℃, initial setting time 15-20min

[0107] Scope of application: Airport runway repair and reinforcement

[0108] Manufacturer: A company in Chongqing

[0109] 1. Product performance

[0110] Tongtong No. 1 is a concentrated polymer type rapid structural repair material. It is an ultra-early strength concrete structure repair material made with cement as the base binder, high-strength material (quartz sand) as the main aggregate, supplemented by polymer glue powder, high-efficiency water reducing agent, early strength agent, expansion agent, anti-segregation and other substances.

[0111] The product has the characteristics of good self-flowability, fast hardening, early strength, high strength, no shrinkage, slight expansion; non-toxic, harmless, non-aging, no pollution to water quality and surrounding environment, good self-tightness and rust resistance.

[0112] 2. Technical parameters (indicators) see Table 1.

[0113] Table 1

[0114]

[0115] 3. Usage

[0116] (1) Cleaning of damaged board surface: Use a pneumatic pick or electric hammer to break the broken board into small pieces and then remove them. Remove the loose materials on the surrounding board base surface thoroughly, and use a high-pressure fan to blow away the dust on the base surface and in the groove.

[0117] (2) Surface wetting and preheating: 0.5 to 1 hour before pouring the mixture, fully wet the surface with warm water not exceeding 65°C and remove the exposed water with a portable high-pressure hot air blower or heat the pretreated surface with a gas blowtorch.

[0118] (3) Interface treatment: Apply a layer of polymer interface agent evenly on the base surface.

[0119] (4) Simple formwork: For the cement concrete pavement slab located in the middle to be repaired, the surrounding slab edges can be used as formwork; for the cement concrete pavement slab located at the edge to be repaired, the three sides can use the surrounding slab edges as formwork. The edges should be supported by wooden or steel formwork, and measures should be taken to prevent leakage.

[0120] (5) Preparation and mixing of repair materials: According to the number of on-site pouring and pouring speed, the repair materials are manually put into the forced mortar mixer. After dry mixing for 10 seconds, the water amount specified in the product is weighed and mixed with water twice: 2 / 3 water is added for the first time and mixed for 30 seconds; 1 / 3 water is added for the second time and mixed for 150 seconds. After mixing, the repair materials should be left to stand for 2 to 3 minutes and poured after the bubbles disappear.

[0121] (6) Pouring of repair material: Use a pouring container to pour the material slowly and evenly to make it dense, and avoid hollowing during pouring. After pouring, smooth the top surface of the repair material. The time from the start of mixing to the end of pouring of the repair material each time shall not exceed 30 minutes. Repair material that has exceeded the time limit or whose fluidity does not meet the pouring requirements shall not be used.

[0122] (7) Finishing and roughening: After pouring and leveling with the board surface, finish the surface immediately and roughen it along the texture direction of the board surface to maintain the overall aesthetics.

[0123] (8) Health preservation: Use straw mats or quilts to cover and keep warm for 2-4 hours.

[0124] The material Figure 4 As shown, 25kg / bag, including aggregate

[0125] Proposed material three

[0126] Product name: Special repair material for airport pavement (BC type / JC type / SC type / QR type, etc.)

[0127] Applicable ambient temperature: -10℃~-20℃, initial setting time 15-20min

[0128] Scope of application: Repair and renovation of airport runways, taxiing areas, aprons, supporting areas, buildings, etc.

[0129] High-performance polymer grouting materials for settlement, voiding and misalignment of road slab blocks;

[0130] Airport panel crushing and rapid plate replacement, high performance rapid plate replacement HB type;

[0131] Repair of frozen and thawed pavement peeling and pockmarked surface, high-performance BC type pavement or JC type runway surface repair material;

[0132] High-performance SC type pavement or QR type runway deep structure repair material for pavement edge chipping, potholes, cracks and broken panels.

[0133] Manufacturer: A company in Henan

[0134] 1. Product performance and technical parameters

[0135] (1) Strong bonding strength: up to 2.8MPa or more, ensuring that it does not fall off under heavy load and high impact conditions;

[0136] (2) No shrinkage cracks: The material has a high water retention rate and no shrinkage cracks after repair. It is suitable for use in high-altitude areas and places with large temperature differences between day and night;

[0137] (3) Compression and wear resistance: The compressive strength is above 60MPa, and the heavy-load road surface will not crack or break when rolled over;

[0138] (4) Low elastic modulus and high toughness: Low elastic modulus and high toughness, impact resistance can reach more than 8 times that of ordinary concrete;

[0139] (5) Anti-seepage and anti-freezing: The anti-freezing property is above F200, and the skin will not fall off when soaked in water, thus preventing the road surface from freezing and thawing due to high cold weather;

[0140] (6) Chloride salt corrosion resistance: Resistance to snow melting agent corrosion, especially in northern regions, must be resistant to snow melting agent corrosion to be more durable;

[0141] (7) Consistency of thermal expansion and contraction coefficients: Ensure that the thermal and hot cycles produce synchronous displacement with the original concrete pavement to prevent inconsistent thermal expansion and contraction coefficients from causing poor bonding, falling off, etc.

[0142] 2. Usage

[0143] Refer to the proposed material 2

[0144] 3. Research material sample test situation

[0145] 1. General test conditions

[0146] (1) The external environment temperature of mixing and processing is 8-10℃;

[0147] (2) The mixing water is an ice-water mixture with a temperature of 0°C ± 2°C;

[0148] (3) The mixing and preparation time is about 6 to 8 minutes, and the specimen size is 40 mm × 40 mm × 160 mm;

[0149] (4) After rapid molding, the molded specimens are placed in a freeze-thaw box at a temperature of -10 to 20°C, and strength tests are performed on the molded specimens after 2 h, 3 h, and 4 h.

[0150] The experimental process is as follows Figure 5-Figure 16 shown.

[0151] The results are shown in Table 2.

[0152] Table 2 Comparative analysis

[0153]

[0154]

[0155] According to the comparative analysis of the tests, the strength growth (compressive and flexural strength), construction performance and other technical parameters of the three material samples of the proposed material 1, the proposed material 2 and the proposed material 3 can all reach the expected goals at the set ambient temperature (-10 to -20°C) and within the limited time, but the setting time is generally short, especially the proposed material 1, and the optimization adjustment range is limited. It is a great challenge to the workers' operating proficiency and construction organization during construction.

[0156] The preferred specific implementation modes and embodiments of the present invention are described in detail above, but the present invention is not limited to the above implementation modes and embodiments, and various changes can be made within the knowledge scope of those skilled in the art without departing from the concept of the present invention.

Claims

1. Testing and selection method of low temperature rapid repair material, characterized in that: The following steps are involved: S01, determine the general conditions of the test; S02, classify the potholes according to their depth, determine the low-temperature rapid repair material, and conduct repair and performance testing; S03, select the low-temperature rapid repair material based on the performance test results and the price.

2. The method for testing and selecting low-temperature rapid repair materials according to claim 1, characterized in that: In S01, the general test conditions include at least one of the following: (1) The external environment temperature of mixing and processing is 8-10℃; (2) The mixing water is an ice-water mixture with a temperature of 0°C ± 2°C; (3) The mixing and preparation time is 6 to 8 minutes, and the specimen size is 40 mm × 40 mm × 160 mm; (4) After rapid molding, the molded specimens are placed in a freeze-thaw box at a temperature of -10 to -20°C, and strength tests are performed on the molded specimens after 2 h, 3 h, and 4 h.

3. The method for testing and selecting low-temperature rapid repair materials according to claim 1 or 2, characterized in that: In S02, the depth of the repaired pothole includes a shallow repair pothole depth of ≤5 cm and a deep repair pothole depth of >5 cm.

4. The method for testing and selecting low-temperature rapid repair materials according to any one of claims 1 to 3, characterized in that: In S02, for shallow repairs with a depth of ≤5 cm, use a low-temperature rapid repair material without coarse aggregate, or use a test sieve to remove coarse aggregate to form a low-temperature rapid repair material without coarse aggregate; Preferably, a test sieve with a mesh size of 2.36 mm is used.

5. The method for testing and selecting low-temperature rapid repair materials according to any one of claims 1 to 4, characterized in that: In S02, for deep repairs of potholes with a depth of more than 5 cm, use low-temperature rapid repair materials containing coarse aggregates, or low-temperature rapid repair materials without coarse aggregates with the addition of crushed stone; Preferably, the crushed stone is a continuously graded crushed stone; Preferably, the aggregate particle size in the low-temperature rapid repair material containing coarse aggregate is 4.75-9.5 mm.

6. The method for testing and selecting low-temperature rapid repair materials according to any one of claims 1 to 5, characterized in that: In S02, for shallow repairs with a pothole depth of ≤5 cm, the performance tests performed after repair include early strength; Preferably, the early strength includes at least one of 2h, 3h compressive strength and 2h, 3h flexural strength.

7. The method for testing and selecting low-temperature rapid repair materials according to any one of claims 1 to 6, characterized in that: In S02, for deep repairs with a pothole depth of more than 5 cm, the performance test performed after the repair includes at least one of early strength, shrinkage performance, initial setting and final setting time, workability and appearance; Preferably, the early strength includes at least one of 2h, 3h, 4h compressive strength and 2h, 3h, 4h flexural strength; Preferably, the working properties are early hydration heat, setting time, fluidity, and workability; Preferably, the appearance includes the color difference with the original concrete and the adhesion between the new and old joint surfaces.

8. The method for testing and selecting low-temperature rapid repair materials according to any one of claims 1 to 7, characterized in that: S02 includes the steps of repairing the surface, calculating the amount of materials, premixing the materials, optionally adding stones, mixing with water, and vibrating the surface; Preferably, the repair surface treatment is to cut and remove the damaged part to the hard layer, and the depth of the removal is determined according to the actual situation. The surface of the pit after treatment shall not have cracks, loose gravel, floating dust, oil stains, and accumulated water; Preferably, when the repair depth is ≥5cm, stones are added to make concrete, and the weight ratio of the repair mixture to stones is controlled at 100:50-80, and the stones are clean crushed stones with a continuous gradation of 5-30mm in particle size; Preferably, 5.5% to 7% of water by weight of the low-temperature rapid repair material is added at one time and stirred until the mixture has good fluidity and cohesiveness; Preferably, the evenly mixed material is placed into the pit to be repaired and compacted with a flat plate vibrator or a vibrating rod, and the surface is quickly prepared before initial setting.

9. The method for testing and selecting low-temperature rapid repair materials according to any one of claims 1 to 7, characterized in that: In S02, the repair area extends 5 to 10 cm outward from the disease-affected area, and the repair size is a regular rectangle with a length-to-width ratio of less than 3:1; Preferably, patches with irregular plane dimensions or a length-to-width ratio greater than 3:1 should be repaired in multiple times to ensure that each patch meets the size requirements; or they can be repaired in one go and cut promptly after pouring. After cutting, the patches should meet the requirement of a length-to-width ratio of 3:

1.

10. The method for testing and selecting low-temperature rapid repair materials according to any one of claims 1 to 7, characterized in that: S02 includes the steps of cleaning the damaged board surface, wetting and preheating the base surface, interface treatment, simple formwork, mixing the repair material, pouring the repair material, finishing and roughening, and curing; Preferably, the crushing plate body is broken into small pieces by a pneumatic pick or electric hammer and then removed, loose materials on the surrounding plate body base surface are completely removed, and dust on the base surface and in the groove is blown away by a high-pressure blower; Preferably, 0.5-1 hour before pouring the mixture, the base surface is fully moistened with warm water not exceeding 65°C and the exposed water is removed with a portable high-pressure hot air blower or the pre-treated base surface is heated with a gas burner; Preferably, a layer of polymer interface agent is evenly applied on the base surface; Preferably, for the cement concrete pavement panel to be repaired in the middle, the surrounding panel edges are used as templates; for the cement concrete pavement panel to be repaired at the edge, the three sides thereof use the surrounding panel edges as templates, the edges are supported by wooden or steel templates, and anti-leakage slurry measures are taken; Preferably, according to the number of on-site pouring and pouring speed, the repair material is manually put into the forced mortar mixer, dry mixed for 10 seconds, weighed according to the water amount specified in the product, and mixed with water twice: add 2 / 3 water for the first time and mix for 30 seconds; add 1 / 3 water for the second time and mix for 150 seconds. After mixing, the repair material should be left to stand for 2 to 3 minutes, and then pour after the bubbles disappear; Preferably, pour the material slowly and evenly with a pouring container to make it dense, and avoid hollowing during pouring; after pouring, smooth the top surface of the repair material; The time from the start of mixing to the end of pouring of the repair material each time shall not exceed 30 minutes; repair materials that exceed the time limit or whose fluidity does not meet the pouring requirements shall not be used any more; Preferably, after pouring and flushing with the board surface, the surface is immediately closed and roughened along the texture direction of the road panel surface to maintain the overall aesthetics; Preferably, straw mats or quilts are used to cover and keep warm for 2 to 4 hours.